Manual handling in the food industry - Lovitt, Zane; Collins, Cath; Boland, Michael; Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 2006)
This program combines interviews with OH&S practitioners and footage of applied manual handling including hazard identification, risk assessment and risk control as it relates to the food industry
Executive producer, Mark McAuliffe ; senior producer, Richard Leigh
Voice over: Michael Szue
DVD format
Keywords: Food handling; Food industry and trade; Materials handling; Lifting and carrying